Perkembangan Masa Remaja - Oriza Latifah; Rahmadani Rahmadani; Linda Yarni (Universitas 45 Surabaya, 2024)
Adolescent development is an important transition phase in an individual's life, characterized by significant physical, cognitive, emotional, and social changes. This phase marks the beginning of maturity and self-identity, with unique challenges and opportunities. Physical development includes body growth and sexual development, while cognitive development includes the ability to think abstractly and solve problems. The emotional aspects of adolescence often involve emotional turmoil and the search for identity, while the social aspects involve exploration of social relationships and the formation of social identities.